Metastatic uterine leiomyosarcoma coexisting with papillary carcinoma of the thyroid gland. Issue 1 (1st January 2006) - Giannikaki, E.; Mantadakis, E.; Mamalaki, E.; Delides, G.; Samonis, G.
Abstract : Metastatic leiomyosarcoma to the thyroid gland has rarely been described. We report a 54-year-old postmenopausal woman with uterine leiomyosarcoma, who presented with a single "cold" nodule in the right thyroid lobe 3 months after hysterectomy. The lesion was identified as a papillary thyroid carcinoma. In a separate area of the thyroid, a 1.2-mm area of a malignant mesenchymal neoplasm with morphologic and immunohistochemical features of leiomyosarcoma existed. Seven months after thyroidectomy the patient developed micronodular lung disease visible on successive chest computed tomography scans, consistent with metastatic disease from the primary uterine leiomyosarcoma that showed very good and prolonged response to chemotherapy. The thyroid papillary carcinoma was likely the recipient of an early and possibly the first metastasis of the patient's uterine leiomyosarcoma. This is the first report of metastatic leiomyosarcoma coexisting with a primary thyroid carcinoma and supports the possibility of a common pathway connecting thyroid gland neoplasms and sarcomas.